Review Of Laws and Decisions of the Indonesian Competition Commission on Notification Obligations - Patricia Mutiara (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This article examines the legal consequences of a delayed notification of a share acquisition under Indonesian competition law, focusing on the case of PT X's takeover of PT Y. The central issue is PT X's failure to report the acquisition to the Commission for the Supervision of Business Competition (KPPU) within the mandated 30-day period, as stipulated by Law Number 5 of 1999 and its implementing regulation, Government Regulation Number 57 of 2010. The notification was submitted with a significant delay of 2,023 days, a clear violation of the statutory requirements. As a result of this non-compliance, the KPPU, through its Decision No. 31/KPPU-M/2020, imposed an administrative fine on PT X amounting to IDR 1,050,000,000.00 (one billion fifty million rupiah). Beyond the direct financial penalty, the violation led to severe indirect repercussions, including significant reputational damage, which threatened to erode investor confidence and disrupt existing business relationships. The KPPU's firm and consistent enforcement in this case highlights the critical function of the post-merger notification system in Indonesia as a preventative mechanism to assess transactions that could lead to excessive market concentration. The decision underscores the legal principles of transparency, fairness, and accountability that underpin Indonesian competition law. This case serves as a powerful deterrent, signaling to all business actors that non-compliance will not be tolerated. Ultimately, such rigorous enforcement is crucial for fostering a culture of legal adherence, maintaining market integrity, and building a more transparent and competitive business ecosystem that supports sustainable economic growth in Indonesia.